Thyroid hormone status in children with protein energy malnutrition a hospital based case control study - Dhanjal, Gurdeep S.; Singh, Mrigind (International Journal of Contemporary Pediatrics, 2017)
Background: WHO estimates that about half of all deaths, occurring among children aged less than five years in the developing countries, can be attributed to malnutrition. In malnourished children various endocrinal changes are noted. There is reduced synthesis of plasma proteins that affects secretion and metabolism of thyroid hormone. The present study has been conducted to study the effect of protein energy malnutrition (PEM) on thyroid hormone and plasma protein levels; and to find correlation between thyroid hormones and plasma protein levels in PEM children. Methods: A cross sectional hospital based case-control study was carried out in tertiary care hospital of Northern India. 50 children with PEM, and equal number of age and sex matched healthy controls (1-5 years) were included in the study. Detailed clinical assessment of nutritional status followed by anthropometric measurement was recorded in a predesigned performa. The cases were categorized into moderate and severe malnutrition as per WHO classification (weight for height). Free Triiodothyronine (fT3), free Thyroxine (fT4), thyroid stimulating hormone (TSH), serum total protein and serum albumin were estimated. The parameters were compared among cases and controls using appropriate statistical tool. Results: Mean hemoglobin, serum protein, serum albumin, fT3, fT4 and TSH levels were significantly low in case group, when compared to the control group (p <0.001).The levels of biochemical variables, decreases as the severity of malnutrition increases. The difference within the cases (moderate and severe malnutrition) was also found to be statistically significant (p <0.001). Conclusions: PEM is associated with decrease level of thyroid hormone levels and were positively correlated with serum total protein and albumin levels. The decrease level of thyroid hormone may have a contributory role in retarded growth and development.